Selective rescaling, inequality and popular growth coalitions: The case of the Israeli national plan for earthquake preparedness. (December 2020) - Margalit, Talia; Mualam, Nir
Highlights: The Israeli government initiated an experimental nation-wide plan for earthquake preparedness. With this policy, the government re-centralized planning by circumventing local plans. At the same time, planning was decentralized by empowering apartment owners to initiate development. Projects are not feasible in peripheral, less affluent and at-risk earthquake areas (causing socio-spatial divides). This selective, centralized-decentralized policy encourages popular growth coalitions in central (core) cities. Abstract: What happens when a government decides to up-zone an entire country and give apartment owners nationwide incentives to upgrade their homes? Can such a plan benefit everyone? What happens when it does not? We discuss these questions by analyzing TAMA 38, a nationwide statutory plan approved in Israel in 2005. With this plan, the central government encourages apartment owners of older buildings (built before 1980) to make them earthquake-ready by giving them options to add floors and space, and to cooperate with developers who will renovate the properties. The plan is a strictly entrepreneurial undertaking that depends entirely on land values and private market actors. At the same time, to expedite the implementation of the policy, the central government performed a bold scalar jump, bypassing both local and district planning levels and allowing owners to acquire building permits regardless of local plans, conditions, and regulations. We discuss this plan in light of the literature on rescaling in planning. Scholars show that following decades of growing neoliberal decentralization, various central governments are now advocating a variety of centralized-decentralized policies that bypass local decision-making and/or strategically blur national, district, and local planning scales. As in the case of TAMA 38, such methods perpetuate the neoliberal dependence on market agents, and prioritize specific actors, places and projects. By analyzing the implementation of this policy, we show how such methods create uneven development and power conflicts between actors from different planning tiers. Ultimately, we demonstrate that regardless of nationwide goals of earthquake preparedness, planners focus on central locations and affluent actors, while meaningful questions about equality and scale are sidestepped and ultimately forgotten.